Influence of Marangoni convection, solar radiation, and viscous dissipation on the bioconvection couple stress flow of the hybrid nanofluid over a shrinking surface - Rehman, Ali; Khan, Waris; Abdelrahman, Anas; Jan, Rashid; Khan, Muhammad Sohail; Galal, Ahmed M. (Frontiers in Materials, 2022)
The heat transfer ratio plays an important role in industries and the engineering sector, in this model the authors used the hybrid nanofluid because the heat transfer ratio of hybrid nanofluid is more as compared to the base fluid, the key objective of this research work is to boost up the heat transfer ratio. for example, the accomplishment of energy is not enough, but also to regulate the feedings of energy and this is possible only to approve the development heat transmission liquids to mechanism the expenditures of energy and to improvement. The current research paper investigates the influence of marangoni convection, solar radiation, and viscous dissipation on bioconvection couple stress flow of hybrid nanofluid over a shrinking surface. This type of flow has some important application in industries sector and engineering sector for the purpose of cooling and hotness effect. To transform the non- dimensionless form of the differential equation to the dimensionless form of the differential equation, the authors used the defined similarity transformation. The transform dimensionless form of the differential equation is solved by the homotopic analysis method. The important obtained result is taken with the help of graphs which is obtained from velocity and temperature equations. The impression of different parameters such as couple stress parameter, marangoni convection parameter, nanoparticle volume fraction, solar radiation parameter, magnetic field parameter, thermophores parameter, Eckert number, and Prandtl number are taken over graphs. The skin friction coefficient and Nusselt number are described in the form of tables.